Implementation of Rehabilitation System of Prisoner for the Prisoner Resocialization in the Correctional Institution Class II A Palopo - H Hamsir; Z Zainuddin; A Abdain (Faculty of Law, Universitas Jenderal Soedirman, 2019)
Implementation of rehabilitation for prisoners in an effort to return prisoners to a good society is very important to do, not only material or spiritual, but both must be balanced. The problem in this study was how to implement a prisoner rehabilitation system so that inmates were aware of mistakes, improved themselves and did not repeat criminal acts in correctional institution Class IIA Palopo. This type of research is empirical legal research that is descriptive qualitative. The implementation of rehabilitation in the correctional system affects the prisoners who undergo their criminal periods while in prison. Guidance of prisoners in Prison Class IIA Palopo is carried out through personality development which includes (religious formation, legal awareness development), and self-development including prisoner skills training and assimilation processes. The research recommendation is that penitentiary Officers intensify the formation of personality and independence of prisoners with the aim of no longer committing crimes and can socialize themselves inmates in the community. In addition, it is necessary to collaborate with the Ministry of Religion to intensify the religious rehabilitation of prisoners in the context of socialization in the community.Keywords: Penitentiary, Prisoners, and Rehabilitation.